Cisplatin and 5-Fluorouracil Inhibits 6-Phosphogluconate Dehydrogenase Activity in Human Erythrocytes in vitroand in vivo - OZABACIGIL, FATMA; BEYDEMIR, SUKRU; CIFTCI, MEHMET; GUMUSTEKIN, KENAN; BAKAN, NURI (Asian Journal of Chemistry, 2010)
The antineoplastic agents cisplatin and 5-fluorouracil, have been used frequently in the medical treatments of various cancers. Cisplatin is an important drug that is administrated in the treatment of metastatic tumours of the testis, ovaries and solid tumors. 5-Fluorouracil is used in combination therapy for the treatment of some cancers including head and neck. In this study, in vitro effects of these drugs on human erythro-cytes 6-phospogluconate dehydrogenase (6PGD) and in vivo effects on rabbit erythrocytes 6PGD activity were investigated. For this purpose, human erythrocyte 6PGD was purified with 0.46 U/mg protein specific activity, 50 % yield and approximately 742-fold using 35-65 % ammonium sulfate precipitation and 2',5'-ADP Sepharose 4B affinity chromatography. The enzyme activity was determined by Beutler's method. To check the purity of enzyme, SDS-polyacrylamide gel electrophoresis was performed. For the drugs, in vitro inhibition studies were performed and activity % - [Drug] graphs were drawn. IC50 values were calculated as 1.49 mM for cisplatin and 62.5 mM for 5-fluorouracil from these graphs. Then, Ki values for cisplatin and 5-fluorouracil were also calculated from Lineweaver-Burk graphs as 1.35 ± 0.206, 53.8 ± 10.53 mM, respectively and inhibition types of the drugs were found out to be uncompetitive manner. In addition, timedependent in vivo studies were executed for the drugs in New Zealandalbino rabbits. Cisplatin at 1 mg/kg inhibited the enzyme activity significantly (p < 0.01) 3 and 5 h after dosing. 5-fluorouracil at 25 mg/kg inhibited the enzyme activity significantly (p < 0.01) 1, 3 and 5 h after dosing. As seen from obtained IC50 and Ki values that the purified human 6PGD has been quite inhibited by these drugs.